Pengembangan Model Pembelajaran Membaca Kritis Berbasis Inkuiri untuk Meningkatkan Keterampilan Membaca Kritis - Cahyani, Regita Purnama; Ramly, Ramly; Sakaria, Sakaria (Nuances of Indonesian Language, 2024)
This research and development aims to: (1) obtain comprehensive information regarding the design of an inquiry-based critical reading learning model to improve critical reading skills, (2) produce a product in the form of an inquirybased critical reading learning model book. This type of research is Research and Development (R&D), with a 4D model development design (Define, Design, Defelopment, and Dessimination). The data from this research are qualitative and quantitative data. Qualitative data comes from comments, criticism and suggestions from expert and practitioner assessments of model books. Quantitative data comes from expert and practitioner assessments of model books. The data analysis technique for this research is qualitative and quantitative data analysis. Qualitative data analysis, namely grouping and concluding data in the form of comments, criticism and suggestions from media improvement experts and practitioners and quantitative data analysis, namely finding the average of each expert assessment indicator for the suitability of the model book. The results of this research are the design of an inquiry-based critical reading learning model with eight learning syntaxes, namely: (1) problem presentation; (2) hypothesis formation; (3) conceptualization of steps; (4) information collection; (5) information analysis; (6) reading evaluation; (7) statement of ideas; and (8) selfreflection. The results of expert assessments and inquiry-based critical reading model books show feasibility by obtaining an average of 0.93 in the very feasible category. The results of the expert assessment of the model book show an assessment in the very appropriate category.